Studies on the Importance of the 7α-, and 12α- hydroxyl groups of N-Aryl-3α, 7α, 12α-trihydroxy-5β-cholan-24-amides on their Antigermination Activity Against a Hypervirulent Strain of Clostridioides (Clostridium) difficile. (15th December 2021) - Sharma, Shiv K.; Yip, Christopher; Simon, Matthew P.; Phan, Jacqueline; Abel-Santos, Ernesto; Firestine, Steven M.
Graphical abstract: Abstract: Chenodeoxycholic acid (CDCA) is a natural germination inhibitor for C. difficile spores. In our previous study ( J. Med. Chem., 2018, 61, 6759–6778), we identified N-phenyl-3α, 7α, 12α-trihydroxy-5β-cholan-24-amide as an inhibitor of C. difficile strain R20291 with an IC50 of 1.8 μM. Studies of bile salts on spore germination have shown that chenodeoxycholate, ursodeoxycholate and lithocholate are more potent inhibitors of germination compared to cholate. Given this, we created amide analogs of chenodeoxycholic, deoxycholic, lithocholic and ursodeoxycholic acids using amines identified from our previous studies. We found that chenodeoxy- and deoxycholate derivatives were active with potencies equivalent to those for cholanamides. This indicates that only 2 out of the 3 hydroxyl groups are needed for activity and that the alpha stereochemistry at position 7 is required for inhibition of spore germination.